EFFECT OF PLOT SIZE ON ABOVE-GROUND CARBON STOCK ESTIMATES IN BERAU - Ali Suhardiman; Yosep Ruslim; Nur Fajrin (Forestry Study Program University Of Mataram, 2026)
In designing data collection methods to estimate carbon stocks stored above and below the forest surface, plot size is a crucial factor that needs to be considered. This study aims to evaluate the effect of plot size differences on the results of above-ground carbon stock estimates at PT Wana Bakti Persada Utama, Berau Regency, East Kalimantan. This study is important because plot size is a fundamental component in forest inventory design that directly affects the accuracy, stability, and representativeness of carbon estimates. The selection of an inappropriate plot size can cause bias, either in the from of overestimation or underestimation of carbon stocks, thereby impacting the accuracy of data in supporting forest management planning and climate change mitigation. Data collection was carried out using a rectangular nested plot design with three sizes, namely (20×20 m), (20×50 m), and (20×100 m), for a total of 15 plots. All trees with a Diameter at Breast Height (DBH) ≥ 40 cm were measured and their above-ground biomass was calculated, then converted into carbon stocks. The results showed that the average carbon stock in small, medium, and large plots was 67.59 ± 22.21 tonsC/ha; 86.81 ± 37.51 tonsC/ha; and 89.67 ± 36.34 tonsC/ha, respectively. The t-test results show that there is no significant difference between plot sizes (α = 0.05), except between small and large plots. These findings confirm that plot size affects the accuracy of carbon stock estimates and needs to be carefully considered in the design of forest carbon inventories.